Lecturers’ Perceptions on the Utilization of Translation Rubrics for Guiding Peer and Self-Assessment in Higher Education - Handayani, Witri; Saptopramono, Hendro; Apriyanti, Difiani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Abstract Evaluating translation skills in students is challenging due to difficulties in maintaining fairness and providing proper feedback. This study examines the perspectives of college teachers on using translation rubrics to guide self-assessment and peer assessment among students. Interviews with two instructors from Politeknik Negeri Padang showed that rubrics are crucial tools for conducting fair and organized evaluations. These rubrics reduce bias and clarify what is expected by focusing on key aspects like translation accuracy, readability, and maintaining the original meaning. Both instructors agree that students assessing their own work and others' is beneficial because it enhances editing skills and increases their understanding of translation. Despite this, there are some challenges. People might interpret rubric criteria in different ways, time for assessment can be tight, and existing technology doesn't always meet the needs. Nevertheless, digital tools such as MS Word and Google Docs are considered helpful in simplifying the process. The study stresses the importance of having uniform rubrics and technological support to improve the teaching of translation and encourage students to become more independent learners. Keywords: Lecturers’ Perceptions, Peer Assessment, Rubrics, Self-Assessment, Translation Assessment.